Assessment Activity Concentrations of Rice Components (Root, Stem, Leaf, and Grain) and Transfer Factors (TF) from Paddy Soil to Rice Grain of Radionuclides 40K, 226Ra, 232Th, and 137Cs Investigation in Taiwan - Wei-Hsiang Huang; Ting-Chien Chen; Sheng-Chi Lin; Zhi-Mou Chen; Yi-Lung Yeh (Agronomy, 2024)
This study analyzed the activity concentrations of various radionuclides in irrigation water, rice components, and corresponding soil samples from eleven paddy fields, revealing significant findings with potential environmental and health implications. The soil exhibited high levels of activity concentrations ranging from 350 to 829, 12.4 to 41.2, and 18.5 to 60.3 Bq/kg, with mean values of 609, 31.1, and 45.0 Bq/kg for 40K, 226Ra, and 232Th respectively. Additionally, 12 soil samples from two paddy fields showed 137Cs activity concentrations of 5.6 ± 1.3 Bq/kg. The rice plant roots accumulated the highest percentages of total activity concentrations for 226Ra, 232Th, and 137Cs, ranging from 76–86%, while only 1.1–10.0% were found in the un-hulled grain. For 40K, activity concentrations were distributed among the root (23%), stem (32%), leaf (35%), and un-hulled grain (10%). The mean activity concentrations were 99 ± 12, 0.49 ± 0.09, 0.43 ± 0.12, and 0.10–0.31 Bq/kg for 40K, 226Ra, 232Th, and 137Cs for un-hulled rice grain, respectively. Transfer factors (TFs) from soil to un-hulled rice grain were calculated as (1.21–2.86) × 10−1 for 40K, (0.07–0.11) × 10−1 for 232Th, (0.11–0.29) × 10−1 for 226Ra, and (0.16–0.61) × 10−1 for 137Cs. Notably, significant negative correlations were observed between TFs and soil concentrations for 40K (r = 0.92, p < 0.001, n = 11) and 226Ra (r = 0.98, p = 0.026, n = 4), suggesting that macronutrients in soil solutions may inhibit the linear transfer of natural nuclides from the soil solution to rice plants.